An Efficient Banking System for Cooperative Banks - Honkanadavar, Nandadevi M; Patil, Anita S (International Journal of Computer Sciences and Engineering, 2025)
Cooperative banks are an important and growing part of many financial systems. Co-operative banking Sector is an important constituent of Multi Agency banking system operation in the country. These sectors play an important role in the economic enlistment of lower and middle income group of people.Co-operative banks are contributing the constituent part in the India’s banking and financial system. In present times all major economic transactions have started taking place digitally. The major trend of modern digital transactions is substantiated by use of database management. The data update is done almost automatically and is much faster. Users in present days can access their accounts directly without going to a bank making transfers, transactions and accessing cash directly without standing in long queues as was prevalent earlier using ATM machines. Agent acts as a bridge between bank and the customer .On employee-side the data is much more organized and accessing and performing actions on user accounts is easier for them. Due to this the bank has better work efficiency and customer experience improves as well.